Unveiling the Epoch: Exploring Pesticide Utilization and Trade Trends Globally and Regionally from 1990 to 2020 - Wisnujati, Nugrahini Susantinah (PT. Sangadji Media Publishing, 2023)
Over the past three decades, a rapid increase in pesticide usage has played a central role in transforming the landscape of modern agriculture. The objective of this research is to conduct a comprehensive analysis of changes in pesticide usage from 1990 to 2020, emphasizing the complexity of global trends, environmental impacts, and pesticide trade dynamics. This study utilizes agri-environmental indicators and relies on the latest statistical data from FAOSTAT in 2022. The applied research method is a quantitative approach based on secondary data.The research findings indicate that global pesticide usage reached 2.7 million tons in 2020, with an average of 1.8 kg/ha. Although reaching a stable level, pesticide trade experienced a significant increase, particularly in the disinfectant category. Over the past three decades, there has been an approximately 50 percent increase in pesticide usage, especially in herbicides. Per capita analysis shows a relatively stable consumption rate, although there is an increase in pesticide usage per unit of agricultural land. Regional levels reveal significant disparities, with Asia as the largest contributor, Europe implementing strict policies, the Americas having the highest usage rates, Oceania experiencing low trade, and Africa applying low usage rates. Some countries, such as Saint Lucia, exhibit high pesticide application rates per unit of agricultural land, and this variation requires in-depth analysis to understand influencing factors. To mitigate negative impacts, international cooperation, the development of sustainable technologies, and a profound understanding of pesticide applications are necessary. Therefore, more effective and sustainable agricultural policies need to be designed to protect the environment and human health.